Polyethylene Oxide as a Multifunctional Binder for High-Performance Ternary Layered Cathodes - Jinshan Mo (MDPI AG, 2021)
Nickel cobalt manganese ternary cathode materials are some of the most promising cathode materials in lithium-ion batteries, due to their high specific capacity, low cost, etc. However, they do have a few disadvantages, such as an unstable cycle performance and a poor rate performance. In this work, polyethylene oxide (PEO) with high ionic conductance and flexibility was utilized as a multifunctional binder to improve the electrochemical performance of LiNi0.6Co0.2Mn0.2O2 cathode materials. Scanning electron microscopy showed that the addition of PEO can greatly improve the adhesion of the electrode components and simultaneously enhance the integrity of the electrode. Thus, the PEO-based electrode (20 wt% PEO in PEO/PVDF) shows a high electronic conductivity of 19.8 S/cm, which is around 15,000 times that of the pristine PVDF-based electrode. Moreover, the PEO-based electrode exhibits better cycling stability and rate performance, i.e., the capacity increases from 131.1 mAh/g to 147.3 mAh/g at 2 C with 20 wt% PEO addition. Electrochemical impedance measurements further indicate that the addition of the PEO binder can reduce the electrode resistance and protect the LiNi0.6Co0.2Mn0.2O2 cathode materials from the liquid electrolyte attack. This work offers a simple yet effective method to improve the cycling performance of the ternary cathode materials by adding an appropriate amount of PEO as a binder in the electrode fabrication process.